Exploring the mechanism of action of Rosa roxburghii Tratt quercetin in ameliorating type 2 diabetes in mice based on the intestinal microbiome and metabolomics - Ziyi Zhao; Yuping Zhu; Lu Nie; Yisha Luo; Shuyi Qiu; Tingyuan Ren (Journal of Functional Foods)
The aim of this study was to evaluate the effect of Rosa roxburghii Tratt (RRT) quercetin on type 2 diabetes mellitus (T2DM). A high-sugar and high-fat diet combined with streptozotocin (STZ) was used to construct a mouse model of T2DM. In this study, level of blood glucose, lipid and inflammatory factors, surface area of the cecum wall, pH and free ammonia, histopathology, and the composition of the intestinal microbiota and metabolites were analyzed. After 28 days of intervention, RRT quercetin significantly (p < 0.05) improved these indicators and ameliorated liver and intestinal damage. And RRT quercetin modulated the relative abundance of harmful and probiotic bacterial genera, and the levels of the differentially abundant metabolites biliverdin, L-homophenylalanine and dihydrofolic acid. The results showed that RRT quercetin could improve insulin resistance, dyslipidemia and the body inflammatory response due to T2DM by regulating the intestinal microenvironment, intestinal flora composition and metabolite levels.